CONTRIBUTION à l’Évaluation du pouvoir antioxydant et de l’activité antimicrobienne de quelques pantes Médicinales - BESSEGHIER Djamel (My University, 2014)
Natural plant extracts contain a variety of phenolic compounds to which are assigned a variety of biological activities. In this context, we attempted to evaluate the antioxidant activity of different extracts prepared from some medicinal plants collected different regions of our country. The antioxidant capacity was evaluated by diphenyl-picrylhydrazyl tests (DPPH) and reducing power of iron (FRAP). The antimicrobial activity of methanol extract of the plants tested was evaluated by the method of diffusion agar medium. The results for the quantitative determination of total polyphenols and flavonoids by colorimetric method allowed to qualify Quercus suber, Periploca laevigata Osyris quadripartita, Salvia officinalis and Crataegus oxyacantha as the richest in phenolic compounds whose content varies between (304.50 ± 0.47 ± 0.28 and 462 mg EAG / g DM), by cons Quercus suber and Rosmarinus officinalis L showed the highest flavonoid content (232.93±1-190.42±1.9mgCE/gDM). The methods of evaluation of the antioxidant activity show that all of the plants tested extracts exhibit antioxidant properties in different levels. The spectrophotometric assay DPPH reduction highlighted 05 active extracts which have the lowest values of IC50 as is the case of méthanolic extracts from: Rosmarinus officinalis; Salvia officinalis; Quercus suber; Crataegus oxyacantha and Periploca laevigata. These values ranging from 15.40 ug / ml to 24.13μg/ml, while the evaluation method of reducing power (FRAP) showed that methanolic extracts tested are grouped into three categories: the most active: Quercus suber; Periploca laevigata (have a high reducing power compared to that of the reference BHA), extracts medium-reducing effect and the lowest with low and lower reducing power than the reference BHA. Antimicrobial activity demonstrated that the Staphylococcus aureus strain is more sensitive to six methanol extracts tested, while the remaining strains are resistant to most of the extracts.
Keywords: Antioxidant; Antimicrobial activity; polyphenols, flavonoids, medicinal plants